House Dust Mites in One of Indonesian Detention Center in 2020 - Ajrina Malia; Makhabbah Jamilatun; Aminah Aminah (Biomedika, 2020)
House dust mite was one of the most common allergens in homes around the world and associated with manifestations of allergies of skin and respiratory tract such as bronchial asthma, allergic rhinitis, and atopic dermatitis. This arthropod was commonly found on carpets, mattresses, children's toys, and other home furnishings. This study was aimed to identify and quantify the number of Dermatophagoides spp in Detention Center. This descriptive study was conducted using flotation method on 52 samples of mattress dust collected in February 2020. The results showed that 49 out of 52 mattress dust samples were positive of Dermatophagoidesspp..Of all Dermatophagoides spp, there were Dermatophagoides pteronyssinus (71.2%) and Dermatophagoides farinae (28.8%). In conclusion, this study found two species of Dermatophagoides spp. in Detention Center and suggested that the fascility maintain the cleanliness of the mattress by drying the mattress and changing the sheets at least once a week.